(untitled) (Transport systems and technologies, 2019)
New methods of information compression have been proposed, namely, probabilistic models of pyramid-linear coding and pyramid-non-linear coding which will significantly improve information storage systems. The task is to change the existing methods, namely, reduce compaction time and save space for storing information on the drive. In the first model of pyramid-linear coding, the time is determined by analyzing all the characters of the input alphabet, and in the second half. In both cases, a significant reduction in compaction time is observed, but in the second case it is 20 ms per 1 kB of information. Also, pyramid-linear coding does not provide for the construction of a code tree, which significantly improves the quality of compaction. The results of the study demonstrate the positive nature of the development of models of pyramidal linear coding and pyramidal non-linear coding, which will make it possible to advance in the field of information technologies and significantly improve information storage and transmission systems. Research in the future will provide significant savings in resources on the use of data storage capacity, as well as solve the issue of time and quality regarding data compression. It should be noted that pyramid-linear coding is the basis for the implementation of completely new and high-quality information processing systems. The development of these systems will fundamentally change the industry and will give a significant impetus to evolution.